An analysis of topics and abilities tested in the Singapore-Cambridge G.C.E. O Level Examinations papers in Additional Mathematics (1966-1972) with pertinent comments of the examiners - Wu, Chook Ying 1929- ([s.n.], 1973)
This study aimed to discover the various topics that are given emphasis in the syllabus of the Singapore-Cambridge General Certificate of Education Ordinary Level Examination. This seminary paper sought to make a descriptive analysis of the actual questions set in the past examination papers in Additional Mathematics for the years 1966 to 1972.